Effects of paclobutrazol concentrations and periods of immersion on garlic crop - de Resende, Geraldo Milanez; Costa, Nivaldo Duarte; de Melo, Natoniel Franklin; de Souza, Rovilson José (Pesquisa Agropecuaria Brasileira, 1999)
This study was carried out from April to September of 1989, in the experimental field of UFLA, Lavras, MG, Brazil, with the objective of evaluating the influence of concentrations and periods of immersion of paclobutrazol on secondary growth control and marketable traits in garlic (Allium sativum L.). The experimental design was a randomized complete block in a 4 x 5 factorial scheme, with four replications. The first factor consisted of paclobutrazol concentrations (0, 500, 1,000 and 1,500 mg L-1 of a.i.), and the second one of periods of immersion (30, 60, 90, 120 and 150 minutes). Reduction in plant height and in number of leaves per plant from 60 to 90 days after planting with paclobutrazol applications was observed. Mean bulb weight increased up to the concentration of 976 mg L-1 of paclobutrazol, and 451 mg L-1 gave the greatest percentage of bulbs of large size. There was no significant difference among treatments for total and commercial yields, percentage of secondary growth bulbs and number of cloves per bulb.